TINJAUAN YURIDIS PEMBERIAN REMISI TERHADAP NARAPIDANA TINDAK PIDANA PENCUCIAN UANG DIKAITKAN DENGAN TUJUAN PEMIDANAAN - Oktaviani, Dwi Putri; Rahmadan, Davit; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The law of its essence is human interest, which is a guideline on how it is fitting for people to do. The negotiation law consists of norms containing negotiations and prohibitions (by the legislators) that have been approved by one of the negotiations which includes negotiations, i.e. negotiations that are specifically related. Punishment is derived from the word legal basis, it can be interpreted as the law for deciding on the law (berechten). Violators of the law are no longer called criminals, are returned as people who are lost, who are fostered in correctional institutions that are issued and are free from their apostasy. Correctional institutions must create a place that commits a crime, repent and good again, because this is a correctional institution in fostering prison residents. Correctional citizens are essentially the same as the community and Indonesian citizens in general who have rights that must be supported. One of the rights that must be protected is the right to remission. Article 14 paragraph (1) letter i of Law Number 12 of 1995 concerning Correctional Facilities which defines one of the prisoners' rights is to obtain a future result (remission). Scientific writing is aimed at: first, to find out how the provisions for granting remissions to convicted money laundering criminals if related to criminal purposes. Second, the ideal provision of remission for convicted money laundering criminals. This type of research used in this study is normative legal research or can be referred to as doctrinal law research. In this normative research, law is conceptualized as what is written in the legislation (law in books) or law is conceptualized as a rule or norm which is a benchmark of human behavior that is considered appropriate. In this normative legal research the writer conducts a research on the level of synchronization of the law, by examining the legislation vertically to reveal the reality, to what extent certain laws are harmonious and the scope is different legislation, which regulates the sphere of life certain (same). From the results of this study it can be concluded that the granting of remission is the right of every fostered citizen in the correctional institution which is the right of every prisoner who has fulfilled the provisions as regulated in the applicable laws and regulations so as to be able to motivate every prisoner serving sentence at the correctional facility.Keywords: Remission, Asset Return, Criminal Purpose